Changes in pre-service teacher self-efficacy for teaching in relation to professional experience placements. Issue 1 (April 2022) - Ma, Kang; McMaugh, Anne; Cavanagh, Michael
This article aims to contribute new, longitudinal evidence on teacher self-efficacy (TSE) by investigating changes in TSE over the last 2 years of an Australian initial teacher education program. Two hundred and one pre-service teachers were surveyed at three timepoints: (1) after the first professional experience placement, (2) before and (3) after the final placement, using the Scale for Teacher Self-Efficacy. Data were analysed using multilevel modelling. TSE for the domains of classroom management and student engagement decreased significantly between the first and before the commencement of the last professional experience placements. All three dimensions of TSE – instructional strategies, student engagement and classroom management – increased significantly during the final placement.